TASAWUF HAMKA SEBAGAI SOLUSI KONTEMPORER UNTUK GEN. Z DITENGAH TANTANGAN BUDAYA POP COGIL DAN CEGIL - Fernanda, Ahmad (JURNAL AL-AQIDAH, 2023)
This research aims to establish modern Sufism, advocated by Buya Hamka, as a solution for navigating toxic lifestyles that foster a culture of arrogance and superficiality. The research method utilized in this article is qualitative, employing a descriptive analysis approach to explore Buya Hamka's thoughts on modern Sufism as a reference for the restless Gen Z generation, troubled by their own existential concerns. Data collection involves the use of questionnaires administered through Google Forms and library research. The primary data sources include processed responses from respondents gathered through Google Forms, while secondary data sources comprise Buya Hamka's book "Tasawuf Modern" and various books and articles accessible via the Open Journal System (OJS). Data analysis techniques entail descriptive analysis utilizing reduction, display, and verification methods. The findings of this writing conclude that Buya Hamka's modern Sufism serves as a suitable solution for Gen Z individuals seeking to transform their toxic and problematic lifestyles. The approach of modern Sufism emphasizes the practice of asceticism within happiness, underscores the importance of education and modesty culture, and emphasizes the maintenance of mental and physical health balance to consistently remember Allah SWT.